A rede de proteção e o enfrentamento à violência doméstica contra crianças e adolescentes - Brito, Inácia Batista de (2016)
The research aimed to analyze from a gender perspective, the work of Managers, Professionals and Counselors that make up the Social Protection Network for Children and Adolescents in the municipality of Itabaianinha/SE, highlighting experiences and challenges faced in the joint, structuring and preventive care actions, to extend the rights and citizenship of children and adolescents victims of domestic violence. The approach of the phenomenon domestic violence against children and adolescents is anchored in full perspective formed by processes, where reality is seen critically, historical, contradictory and dialectical. We seek to break with the idea of domestic violence can be understood only by the appearance of the facts and naturalized as a "social problem" family nature, domestic, where the State is unable to intervene. The qualitative research was conducted with the consultation of bibliographic and documentary sources, giving priority to oral sources through interviews with 14 research subjects: Representatives of Social Protection Network, one Manager of the Municipal Secretariat of Social Assistance, one Manager of the Municipal Department of Education, (01) Manager of the Municipal Department of Health, onr Tutor Counselor, one Representative of the Municipal Children‟s and Adolescents Rights Council, technical staff of CREAS - Specialized Social Assistance Reference Center, consisting of two Social Workers, one Psychologist and one Coordinator, the technical staff of CRAS – Social Assistance Reference Center one Social Worker, one Psychologist and onr Coordinator). The professionals express the importance of vocational training in gender for the performance in social public policies, but do not mention experiments in this way, aimed at multiplying the area, for the children care and groups in vulnerable situations in order to ensure a more humanized care and effective guidance in search of protection and guarantee of rights.